Digital transformation’s role in improving the organisational performance of an Information Technology (IT) company - Stofile, Anati (My University, 2022)
The potential of digital transformation to improve operational efficiencies and stimulate growth has become a critical path for organisations towards improving their competitive advantage. However, digital transformation requires a significant investment before any real financial benefits can be realised. Due to its focus on optimising business operations, an organisation’s operating model must be realigned to enable efficiency improvements of its core business activities through investments in digital technologies. The benefits of digital transformation are extensively covered in business and academic research, but few mention digital transformation costs. Hence, this study evaluates the positive impact that digital transformation has on an organisation's operational performance and financial performance. In addition to improved operational performance, digital transformation has the potential to bring about higher profitability in the long run by lowering operating costs. However, rising operational and integration costs reduce profits in the short to medium term, taking time before positive net benefits are generated. This study contributes to the literature relating to the impact that digital transformation has on the performance of an organisation by exploring the influence of digital maturity factors on operational and financial performance. Furthermore, the analysis reveals that digital transformation has a much more immediate impact on operational performance (operating margin growth) than on financial performance (gross margin growth).
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, 2022
Keywords: Organisational performance; Digital transformation; Operational performance; Digital maturity; Financial performance; SDG-8: Decent work and economic growth